Piotr Dumala의 메조틴트 애니메이션에 나타난 동판화의 제작 기법 연구 - 장서우(Seo-Woo Jang); 김재웅(Jea-Woong Kim) (한국콘텐츠학회 논문지, 17(8), 2017)
Fine art production methods are frequently incorporated into animation production. The Printing Expression method is often employed among fine art production. There are three main techniques in Printing Expression: Silk Screen, Woodcut and Etching. Animations that use Silk Screen and Woodcut techniques are quite common. However, it is rare to find Etching techniques in animations. So with that being said, I would like to introduce etching animation through the work of Piotr Dumala; the well known Ink Etched film director. Also, I analyzed the characters: movement, unique texture and sensuous feeling; that only mezzotinted Etched-Animation expression technique can show. If we can expand methods on how to show our imagination through etching techniques, it can allow many directors to produce etched animation films in which they can express their imagination. 회화적 기법의 제작 방식은 애니메이션에서 종종 활용된다. 그 중 판화의 제작 방식은 애니메이션 제작에 활용 되고 있으며 실크스크린과 목판화는 자주 활용되어 기법 연구의 사례도 많으나 동판화를 활용한 애니메이션의 제작 또는 연구의 사례는 빈약한 실정이다. 따라서 본 연구는 동판화 애니메이션 제작의 교과서적 표본이 되고있는 폴란드의 영화감독이자 표현주의 메조틴트 동판화 애니메이션 감독 피오트르 듀말라(Piotr Dumala)의 작품 사례를 통해 동판화 애니메이션의 제작 기법을 소개 하고자 한다. 메조틴트 동판화만이 표현해 낼 수 있는 독특한 질감과 운동감, 깊이감, 조형적 특징을 분석한다. 애니메이션 작가들에게 동판화 기법을 에칭과 인그레이빙으로 나누어소개함으로써 회화적 애니메이션 제작 기법의 폭을 한 단계 확장시킬 수 있다.